Biological control of grey mould in strawberry fruits by soil Rhizosphere bacterial isolates - Embaby, Mohamed A.; Elsakhawy, Tamer; Abd- Elfatah, Sally I.; Yli-Mattila, Tapani (TAYLOR & FRANCIS LTD, 2025)
The goal of this study was to find effective bacterial isolates possessing antagonistic effects against Botrytis cinerea in strawberry in field conditions and to evaluate the antifungal properties of the extracellular metabolites produced by these isolates. Four bacterial isolates with considerable antifungal activity against B. cinerea were isolated from strawberries collected from local markets in Giza, Egypt. The molecular identification of bacterial isolates indicated that two of the isolates belong to the Bacillus subtilis, while the other two isolates belong to Pseudomonas stutzeri. The supernatants of the isolates were extracted and subjected to GC/MS analysis, which revealed that the supernatants of the isolates contained different types of fatty acids with expected antifungal activity. The most potent B. subtilis strain was further applied as a foliar spray over heavily infected strawberry fields, which led to significant reduction of B. cinerea. Therefore, this strain should be investigated further.